VAXXED & BOOSTED: Increasing COVID-19 Vaccination Rates in West Greenville, NC, USA - Taylor Stamey; Oluwafemi Opelami; Janet Moye (University Library System, University of Pittsburgh, 2024)
Pitt County is ranked 48th out of the 100 counties in North Carolina for COVID-19 vaccination rates, with only 53.8% of the population fully vaccinated. West Greenville, located in Pitt County, is historically of lower economic status, leading to poorer social determinants of health. The goal of the VAXXED & BOOSTED campaign was to increase COVID-19 vaccination rates in West Greenville by combating vaccine hesitancy and easing barriers to vaccination. From June through August of 2022, community ambassadors spoke to members of the community about their vaccine hesitancies and provided them with verified resources about the vaccine. Five vaccination events were hosted at the Community Crossroads Center and the JOY Soup Kitchen throughout July 2022. At each vaccination event, a survey was implemented to determine the effectiveness of the program. Through VAXXED & BOOSTED, 52 people received COVID-19 vaccines: 13 for the first dose, 4 for the second, and 35 for boosters. Of 29 surveyed, 82.8% found community ambassadors helpful, and 51.7% interacted with them before the event. The event influenced 75.9% to get vaccinated, 82.8% learned something new, and 93.1% plan to encourage others to get vaccinated. Word of mouth likely played a significant role in event promotion, as only 51.7% interacted with ambassadors beforehand. The use of community ambassadors and educational events was successful in influencing people to get vaccinated against COVID-19 in West Greenville.